One currency and many modes of wage formation: Why the eurozone is too heterogeneous for the euro - Martin Höpner; Mark Lutter (Max Planck Institute for the Study of Societies, 2014)
Synchronization of national price inflation is the crucial precondition for a well-functioning fixed exchange rate regime. Given the close relationship between wage inflation and price inflation, convergence of price inflation requires the synchronization of wage inflation. Why did the convergence of wage inflation fail during the first ten years of the euro? While differences in economic growth shape the inflation of labor costs, our argument is that the type of wage regime has an additional, independent impact. In coordinated labor market regimes, increases in nominal unit labor costs tended to fall below the ECB's inflation target, while in uncoordinated labor regimes, the respective increases tended to exceed the European inflation target. To show this, we analyze data from 1999-2008 for twelve euro members. We estimate the increases of nominal unit labor costs both in the overall economy and in manufacturing as dependent variables, test a variety of labor- and wage-regime indicators, and control for a battery of economic, political, and institutional variables. Neither the transfer of wage coordination from the North to the South nor the transfer of adjustment pressure from the South to the North is likely to solve the problem of inner-European exchange-rate distortions. – – Die Synchronisation nationaler Inflationsraten ist die entscheidende Voraussetzung für ein funktionsfähiges Regime fester Wechselkurse. Wegen des engen Zusammenhangs zwischen Lohn- und Preisinflation ist hierfür eine Synchronisation der Steigerungen der Lohnstückkosten vonnöten. Warum kam während der ersten zehn Euro-Jahre keine Konvergenz der Lohnauftriebe zustande? Dies lag zum einen an den unterschiedlichen Wachstumsdynamiken der Euro-Teilnehmer, zum anderen an einem institutionellen Unterschied zwischen den Euro-Ländern: den Lohnregimen. In Ländern mit koordinierten Lohnregimen unterschritten die Steigerungen der Lohnstückkosten im Trend das Inflationsziel der Europäischen Zentralbank, in Ländern mit unkoordinierten Lohnregimen fielen die Lohnsteigerungen hingegen höher aus. Um dies zu zeigen, analysieren wir Daten von zwölf Euro-Ländern für die Jahre 1999 bis 2008. Wir betrachten die nominalen Steigerungen der Lohnstückkosten sowohl gesamtwirtschaftlich als auch bezogen auf das verarbeitende Gewerbe und verwenden unterschiedliche Lohnregime-Indikatoren als erklärende Variablen. Zudem kontrollieren wir für zahlreiche ökonomische, politische und institutionelle Kontextbedingungen. Weder eine etwaige Übertragung der Lohnkoordination vom Norden auf den Süden noch eine Übertragung der ökonomischen Anpassungslast vom Süden auf den Norden scheinen geeignet, das Problem der innereuropäischen realen Wechselkursverzerrungen zu lösen.
Keywords: 300